Room temperature nitric oxide sensor actualized from Ru-doped SnO2 nanowires - Ramgir, N. S.; Mulla, Imtiaz S.; Vijayamohanan, K. P. (Sensors and Actuators B - Chemical, 2005)
We report synthesis of the novel Ru-doped SnO2 nanowires and their distinctive response towards NO., and liquefied petroleum gas (LPG) in air. These nanowires have been prepared by a simple approach of evaporation of metal oxide at elevated temperature, The sensor exhibits three order of magnitude changes in the conductivity on exposure to NO2 in air at room temperature, Furthermore. Ru being one of the excellent sensitizers towards LPG these wires also exhibits sensitivity at 250&DEG; C. The amount of Ru plays a crucial role in modulating the sensitivity and lowering the operating temperature. © 2005 Elsevier B.V. All rights reserved.
Keywords: LPG; Nanowires; NO2; tin oxide ruthenium oxide